Sentiment analysis on public opinion of electric vehicles usage in Indonesia using support vector machine algorithms - Poedjimartojo, Naufal Avilandi; Pramesti, Dita; Fa’rifah, Riska Yanu (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2023)
Technological developments in the automotive industry have experienced significant progress in recent years. Currently, many electric vehicles are being produced as an environmentally friendly alternative to vehicles. The use of electric vehicles has become an intense topic of conversation in society, giving rise to various responses and opinions on Twitter. This research aims to analyze Indonesian people's sentiment regarding using electric vehicles through data collected from Twitter. Sentiment analysis is carried out using a machine-learning approach. The best method for pattern recognition problems is a Support Vector Machine (SVM) to sort each comment into positive or negative sentiments. Meanwhile, SVM classification performance was measured using the Confusion Matrix method. In this research, the Synthetic Minority Over-Sampling Technique (SMOTE) method and the Random Undersampling (RUS) method were used to overcome data imbalance. After the model creation and performance evaluation process, the best model produced was the baseline Support Vector Machine with a data sharing ratio of 70:30 without applying imbalance handling techniques. This model achieved an accuracy of 94.8%, a precision value of 95.5%, a recall value of 99.1%, and an F-1 Score value of 97.2%.